Liminal Reproductive Experiences After Therapies for Hematological Malignancy. (March 2015) - Halliday, Lesley E.; Boughton, Maureen A.; Kerridge, Ian
In this article, we discuss the psychosocial health of young women related to fertility, pregnancy, and motherhood after therapies for hematological malignancies. We utilized a hermeneutical phenomenological approach to conduct in-depth interviews with 12 women who had previously received treatment for a hematological malignancy and had experienced uncertainty surrounding their ability to start or extend their biological family. Our presented findings are interpretations of the women's own words as they articulated how they inhabited a liminal space. We concluded that although fertility and motherhood possibly might not be immediate concerns when they received a diagnosis of hematological malignancy, young women could subsequently experience ongoing issues and concerns related to reproductive uncertainty and motherhood capabilities, which have the potential to affect emotionally and psychosocially on their lives. These issues might possibly require longer-term support, counseling, and informational resources. We also discuss the strengths, limitations, and implications of the study.